Revisiting Disciplinary Control in Secondary Schools: The Issue of Corporal Punishment in Calabar South Local Government Area of Cross River State, Nigeria - Ukpabio, Godfrey E.; Usen, Mbon F.; Etor, Comfort (Richtmann Publishing, 2019)
This research investigated the administration of corporal punishment as a disciplinary control mechanism in secondary schools of Nigeria with particular reference to Calabar South Local Government Area of Cross River State, Nigeria. The concept of corporal punishment as a disciplinary control mechanism with the social issues associated with it was discussed. Three hypotheses were formulated to guide the study which adopted survey research design. A questionnaire titled: